2019
DOI: 10.1007/s00294-019-01007-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mechanisms of DNA damage sensing and signaling

Abstract: DNA damage occurs abundantly during normal cellular proliferation. This necessitates that cellular DNA damage response and checkpoint pathways monitor the cellular DNA damage load and that DNA damage signaling is quantitative. Yet, how DNA lesions are counted and converted into a quantitative response remains poorly understood. We have recently obtained insights into this question investigating DNA damage signaling elicited by single-stranded DNA (ssDNA). Intriguingly, our findings suggest that local and globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The "SOS response" in E. coli is initiated by accumulation of single-stranded DNA (ssDNA) during replication of DNA containing lesions (Maslowska et al, 2019). For both bacteria and eukaryotes, Bantele and Pfander (2019) propose a mechanism for responding to DNA damage that is based on the persistence of ssDNA: (1) repair locally if the damage level is low and ssDNA is short-lived; and (2) halt cell division until global repair of high-level damage is accomplished. The overall amount of ssDNA in a given cell must exceed a threshold to activate a DNA damage "checkpoint" for cell division.…”
Section: Damage and Repair Of Organellar Dnamentioning
confidence: 99%
“…The "SOS response" in E. coli is initiated by accumulation of single-stranded DNA (ssDNA) during replication of DNA containing lesions (Maslowska et al, 2019). For both bacteria and eukaryotes, Bantele and Pfander (2019) propose a mechanism for responding to DNA damage that is based on the persistence of ssDNA: (1) repair locally if the damage level is low and ssDNA is short-lived; and (2) halt cell division until global repair of high-level damage is accomplished. The overall amount of ssDNA in a given cell must exceed a threshold to activate a DNA damage "checkpoint" for cell division.…”
Section: Damage and Repair Of Organellar Dnamentioning
confidence: 99%
“…Furthermore, gene body DNA methylation conspires with H3K36me3 to preclude aberrant transcription (47).DNA damage is related to the balance between survival and death in cancer biology (48).As exempli ed in diverse cancers,disruption or deregulation of DNA repair pathways results in genome instability (49).Moreover, the DNA mismatch repair triggers cell cycle arrest in some cases (50).The DNA damage respons makes it safe to play with knives (51). Cell fate regulation is associated with upon DNA damage (52,53). Intriguingly, we clearly identity that mutant MEG3 increases the telomeras activity dependent on DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
“…The ATM-CHK2 and ATR-CHK1 axes also stimulate the transcriptional activity of p53, which promotes a temporary arrest in the cell cycle, thus allowing DNA repair and restoration of homeostasis [ 51 ]. Once the damage is repaired, all these post-translational modifications are reversed to stop the DDR signal [ 13 , 65 , 66 , 67 , 68 ] ( Figure 3 ).…”
Section: Molecular Pathways For Genome Stability Maintenancementioning
confidence: 99%
“…To face DNA damage, cells have evolved a complex set of mechanisms termed DNA damage response (DDR), which allows the detection of the lesions, activates the damage signaling, and regulates the DNA repair [ 13 , 14 ]. It has been suggested that E2 signaling inhibits the DDR to induce chromosomal instability and aneuploidy, which are typical cytogenetic prerequisites for BC initiation and progression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%